Pretreatment Neutrophil-to-Lymphocyte Ratio (NLR) May Predict the Outcomes of Advanced Non-small-cell Lung Cancer (NSCLC) Patients Treated With Immune Checkpoint Inhibitors (ICIs) - Li, Ye; Zhang, Zhibo; Hu, Yi; Yan, Xiang; Song, Qi; Wang, Guoqiang; Chen, Runzhe; Jiao, Shunchang; Wang, Jinliang (Frontiers in Oncology, 2020)
Background Recent studies have demonstrated the predictive value of pretreatment neutrophil-to-lymphocyte ratio (NLR) in advanced cancers, while the role in advanced non-small-cell lung cancer (NSCLC) treated by immune checkpoint inhibitors (ICIs) was still unclear. The aim of this study was to investigate whether pretreatment NLR could predict the outcomes of advanced NSCLC patients treated by ICIs. Methods A comprehensive literature research was first conducted in PubMed, the Cochrane Central library, and Embase for studies that evaluated the association between pretreatment NLR and survival of advanced NSCLC patients with ICIs treatment. We then conducted a retrospective study in Chinese People's Liberation Army (PLA) General Hospital (Beijing, China) to validate the findings. Results In 10 eligible studies, elevated pretreatment NLR was correlated significantly with inferior progression free survival (PFS) (HR = 1.29, 95% CI 1.14-1.46; P < 0.001) and overall survival (OS) (HR = 2.69, 95% CI 1.99-3.65; P < 0.001). Our retrospective study has further shown that pretreatment NLR  6.0 was associated with inferior PFS (median: 5.0 vs 9.1 months, HR = 1.39, 95% CI 1.01-1.91, P = 0.02) and OS (median: 10.0 vs 17.3 months, HR = 1.71, 95% CI 1.18-2.46; P < 0.001). Subgroup analyses stratified by age, gender, ECOG PS, histology, stage, smoking history, treatment and prior lines of therapy were consistent with the above results. Conclusions Our study has confirmed that pretreatment NLR could predict the outcomes of ICIs treatment in patients with advanced NSCLC.